ANALISIS KREDIT BERMASALAH DILIHAT DARI STANDAR NON PERFORMING LOAN (NPL) PADA PT. BANK MANDIRI (PERSERO) TBK - Kurniati, Titi; Nurhayati, Nurhayati (INOVATOR, 2020)
This study aims to examine how much Non Performing Loans at PT. Bank Mandiri (Persero) Tbk registered on the Stock Exchange for the 2014-2018 period. This research method uses descriptive methods including NPL analysis and hypothesis testing using significance test (t test). The results of the study stated that "Non Performing Loans (NPLs) at PT. Bank Mandiri (Persero) Tbk less than 5% than expected ", thus the banks must suppress the Non Performing Loan (NPL) to below 5% according to the health standard Non Performing Loan (NPL) ratio, with the level of Non Performing ratio Loans (NPL) that are low (less than 5%) are categorized as good banks and will also have an effect on increasing bank earnings, and in lending, banks are required to exercise caution because these credit facilities are high risk which can affect the business continuity of PT. Bank Mandiri (Persero) Tbk.